ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT MACET KOPERASI (CU) SOHAGAINI KECAMATAN LAHUSA - Putri Silvia Laia (Jurnal Ekonomi dan Bisnis Nias Selatan, 2022)
The purpose of this study is to describe the factors affecting bad loans in the Sohagaini CU Cooperative, Lahusa District. The type of research used is qualitative type. The data collection technique in this study is an open questionnaire technique. The data analysis method is a qualitative data analysis method with stages, namely data reduction, data presentation and data conclusion. Based on the results of this study, borrowers are stuck with the lack of ability of debtors to manage the funds distributed, lack of document supervision Supporters of loan applications, provide loans to members but not all follow the loan process. The suggestion of this study is that before disbursing loans to members, careful consideration should be given before deciding to provide loans, so as not to harm themselves and not harm the CU Cooperative. Sohagaini, Lahusa District.